Public Knowledge and Practices Regarding Coronavirus Disease 2019: A Cross-Sectional Survey From Pakistan - Saqlain, Muhammad; Ahmed, Ali; Nabi, Ijaz; Gulzar, Aqsa; Naz, Sahar; Munir, Muhammad Muddasir; Ahmed, Zaheer; Kamran, Sohail (Frontiers in Public Health, 2021)
Objectives: Effective mitigation of coronavirus diseases (COVID-19) pandemic requires true adoption of precautionary measures by the masses, that primarily depends upon their knowledge and practices behaviors. The current study aimed to assess the knowledge; practices of Pakistani residents regarding COVID-19 and factors associated with adequate knowledge and positive practices. Material and Methods: A cross-sectional online survey was conducted from 15-April 2020 to 20 May 2020 among 689 Pakistanis by using a validated self-administered questionnaire (Cronbach’s alpha 0.77). The questionnaire included questions on the assessment of demographics, the source of information, knowledge, and practice of COVID-19 on google forms and shared links with the WhatsApp groups, Facebook pages and other online platforms. Regression analysis was applied to find potential predictors of knowledge and practices. Results: Of 689 participants, 431 (62.6%) were male, 64.3% (n=443) were aged less than 30 years, and 328 (47.6%) of participants were married. 48.19% (n=332) had adequate knowledge; 81% (n=555) had positive practices regarding COVID-19 and majority (66.62%, n=459) seek knowledge from social media. Knowledge was significantly higher (OR>1.00, p<0.05) among educated and higher income participants. Positive practices were significantly (OR>1.00, p<0.05) related to the older age (≥50 years), higher education, higher income and good knowledge regarding COVID-19. Conclusion: The study concluded that Pakistani residents had average knowledge and good practices towards COVID-19 yet there are gaps in specific aspects of knowledge, and practice that should be focused in future awareness and educational campaigns. The study recommends the ministry of health authorities to promote all precautionary and preventive measures of COVID-19-consisting of a better-organized approach to all strata of society: less privileged people, older ones and less educated people, in order to have equilibrium of knowledge about COVID-19; hence effective implementation of precautionary measures.